2007
DOI: 10.1007/s00421-007-0569-6
|View full text |Cite
|
Sign up to set email alerts
|

The critical velocity in swimming

Abstract: In supra-maximal exercise to exhaustion, the critical velocity (cv) is conventionally calculated from the slope of the distance (d) versus time (t) relationship: d = I + St. I is assumed to be the distance covered at the expense of the anaerobic capacity, S the speed maintained on the basis of the subject's maximal O(2) uptake (VO2max) This approach is based on two assumptions: (1) the energy cost of locomotion per unit distance (C) is constant and (2) VO2max is attained at the onset of exercise. Here we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 19 publications
(23 reference statements)
0
21
0
5
Order By: Relevance
“…However, other previous studies indicated that CV is faster than the maximal swimming velocity that can be maintained over a long period of time without exhaustion [3,4,5,11] . Therefore, the CV is used by coaches in order to evaluate training eff ects on the whole D-T relationship and on aerobic endurance.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, other previous studies indicated that CV is faster than the maximal swimming velocity that can be maintained over a long period of time without exhaustion [3,4,5,11] . Therefore, the CV is used by coaches in order to evaluate training eff ects on the whole D-T relationship and on aerobic endurance.…”
Section: Discussionmentioning
confidence: 84%
“…In swimming, Wakayoshi et al [22] have applied the CP concept to competitive swimming. It was expressed as the slope of the linear regression line between swimming diff erent distance (D) and its fastest time (T) [3,4,5,11,22,23] . The regression analysis of D and T showed extremely high linearity and a critical velocity (CV) was defi ned as the swimming speed that can be theoretically maintained for a very long time without exhaustion.…”
Section: Introductionmentioning
confidence: 99%
“…Denadai et al (2005) De qualquer forma, a VC pode ser utilizada como referência para a prescrição e controle dos efeitos do treinamento, independentemente dos resultados observados na literatura em relação à sua validade para estimar a MLSS (DI PRAMPERO et al, 2008, DEKERLE et al, 2010. Além da simples metodologia para a sua determinação, a VC parece representar o limite entre os domínios pesado e severo, visto que os atletas provavelmente apresentam estabilidade no consumo de oxigênio (VO 2 ), embora este último possa apresentar um valor maior que o predito pela relação VO 2 versus carga, pelo surgimento do componente lento (CL) quando são submetidos à realização do tempo de exaustão na intensidade de exercício correspondente à VC (CARITÁ et al, 2009 Paulo, v. 11, no 2, p. 128-133, 1997. …”
Section: Protocolo Da Velocidade Crítica (Vc)unclassified
“…6 Increasingly, the critical velocity has been used for swimming coaches as an indicator of aerobic functional capacity of the swimmer, not requiring the use of very expensive and sophisticated equipment or procedures involving lengthy and complex calculations. 6,[8][9][10] Recently, some authors introduced a new trend in critical velocity, associating it with anaerobic performances. [11][12][13] These authors found linear relationships between short swimming distances and their respective times and associations with anaerobic race distances, specifically calling as anaerobic critical velocity.…”
Section: Introductionmentioning
confidence: 99%